2021
DOI: 10.1590/2175-7860202172057
|View full text |Cite
|
Sign up to set email alerts
|

Orchids of the central region of eastern Maranhão, Brazil

Abstract: The eastern portion of the state of Maranhão is a transitional area between Amazon Rainforest, Cerrado and Caatinga. Knowledge about the flora of this region is very poor, especially regarding Orchidaceae. The aim of this study was to provide a survey of the species of this family in the central area of this region. Fieldwork was performed monthly between December 2015 and April 2019 in the municipalities of Aldeias Altas, Caxias, Codó and São João do Sóter. An identification key, morphological descriptions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Our checklist includes 30 species that are not listed in Flora do Brasil 2020 (2020) to the state, however many of them have been recorded in previous publications (Silva et al 1999;Ferreira et al 2017;Rodrigues et al 2019;Saraiva et al 2020;Oliveira et al 2021;Gomes et al 2021;Silva et al in press). Thus, excluding these, a total of six species are cited here for the first time to Maranhão, all also being new records for northeastern Brazil (Tab.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our checklist includes 30 species that are not listed in Flora do Brasil 2020 (2020) to the state, however many of them have been recorded in previous publications (Silva et al 1999;Ferreira et al 2017;Rodrigues et al 2019;Saraiva et al 2020;Oliveira et al 2021;Gomes et al 2021;Silva et al in press). Thus, excluding these, a total of six species are cited here for the first time to Maranhão, all also being new records for northeastern Brazil (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial database was constructed based on the lists provided by Silva et al (1999) andBFG (2015; and new records published more recently (Ferreira et al 2017;Rodrigues et al 2019;Saraiva et al 2020;Oliveira et al 2021;Gomes et al 2021;Silva et al in press). Subsequently, the main Brazilian herbaria and local herbaria were visited (CEN, HABIT, HB, HUEFS, INPA, IAN, MAR, MG, RB, SLUI, SP, SPF, UB, acronyms according to Thiers 2021, continuous adapted) in order to find specimens collected in the state to serve as vouchers of the taxa reported in the literature.…”
Section: Data Collectionmentioning
confidence: 99%
“…Various recent floristic studies confirm that Maranhão is undercollected (Ferreira et al 2017, Ferreira et al 2018, Ferreira et al 2019a, b, Ferreira et al 2022, Gomes et al 2021, Guarçoni et al 2018a, b, Guarçoni et al 2020, Oliveira et al 2021, Scatigna et al 2020. There are few surveys of the fern and lycophyte species in Maranhão (Almeida et al 2020, Silva Junior et al 2020, Fernandes et al 2022, suggesting the need for new botanical studies in the state to update the Flora e Funga do Brasil database, which currently only lists five Selaginella species.…”
Section: Discussionmentioning
confidence: 99%
“…Encyclia gonzalezii bloomed under cultivation between October and November, a time similar to the flowering period mentioned by Meneguzzo et al (2012), i.e., between September and October. Despite the botanical potential of Maranhão, not much research is available about surveying species. Recent studies in Maranhão have shown that, with increasing sampling effort, new records of Orchidaceae (Ferreira et al 2017(Ferreira et al , 2019aGomes et al 2021;Oliveira et al 2021;Pessoa et al in press) and other plant families (Ferreira et al , 2019bGuarçoni et al 2020b;Silva Júnior et al 2020) are discoverable. Even new species are found in Maranhão, as attested by Scatigna et al (2019), Guarçoni et al (2020a), andSantos et al (2020).…”
Section: Discussionmentioning
confidence: 99%